The Effect of Dividend Policy, Debt Maturity, and Operating Cash Flow on Investment Decisions (A Study on Consumer Goods Industry Sub-Sector Companies Listed on The Indonesia Stock Exchange in 2023-2025) - Agus Kubertein; Yohanes Joni Pambelum; M. Ichsan Diarsyad; Iwan Christian (Yayasan Riset dan Pengembangan Intelektual, 2026)
Investment decisions represent one of the most critical strategic policies that determine the direction of corporate growth and long-term sustainability. This study aims to examine and analyze the effect of dividend policy, debt maturity, and operating cash flow on investment decisions in consumer goods industry sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2023–2025. A quantitative approach was employed using secondary data derived from the annual financial statements of the sampled companies. Sample selection was conducted through purposive sampling technique based on predetermined criteria. Data analysis involved classical assumption tests and multiple linear regression using SPSS software. The results indicate that dividend policy has a significant negative effect on investment decisions, implying that an increase in the Dividend Payout Ratio (DPR) tends to constrain investment capacity due to a reduction in retained earnings available for internal financing. In contrast, debt maturity and operating cash flow do not exert a significant effect on investment decisions, suggesting that these two variables are not primary determinants in investment decision-making within this sector. These findings are consistent with the pecking order theory framework, which emphasizes corporate preference for internal sources of financing over external alternatives. This study contributes empirical evidence for academics and practitioners in understanding the dynamics of factors shaping investment decisions in Indonesia's consumer goods industry sector.